Late fungal aneurysm of the deep femoral artery - Carriquiry, Luis; Bergalli, Luis E.; Campos, Néstor; Abó, Juan C. (Cirugía del Uruguay, 1979)
A case of left deep femoral aneurysm was successfully treated by the authors by applying a proximal ligature, opening and performing obliterative endoaneurysmorrhaphy. There follows discussion and acceptance of infections and mycotic origin of condition, with emphasis on its late onset; leading to the conclusion that the main accepted guidelines for treatment of this type of aneurysm should be modified.